Cardioprotective Properties of Ginkgo Biloba Extract 80 via the Activation of AKT/GSK3β/β-Catenin Signaling Pathway - Zheng, XiangWei; Gao, Qi; Liang, Shuang; Zhu, GuoQin; Wang, DanDan; Feng, Yi (Frontiers in Molecular Biosciences, 2021)
Elderly people are more likely to experience myocardial infarction (MI) than young people, with worse post-MI mortality and prognosis. Ginkgo biloba extract 50 (GBE50) is an oral GBE product that matches the German product, EGb761, which has been used to treat acute myocardial infarction (AMI). The extraction purity of GBE50 was improved to form a new formulation, Ginkgo biloba extract 80 (GBE80). This study investigates the effect of GBE80 on aged acute myocardial infarction rats. GBE80 injection is a novel formulation that was prepared by mixing Ginkgo flavonoids and lactones in a 4:1 weight ratio, with a Ginkgo content of more than 80%. Cell Counting Kit-8 was used to determine the biological safety and protective effect of GBE80 on cardiomyocytes against oxidative damage. An aged AMI rat model was developed and used to determine the myocardial infarction weight ratio using triphenyltetrazolium chloride staining. Terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling (TUNEL) was applied to detect cell apoptosis in myocardial tissue. Western blotting and immunohistochemistry were used to measure the protein levels of members of the AKT/GSK3β/β-catenin pathway in vitro and in vivo, respectively. We found that GBE80 in vitro suppressed H2O2-induced cytotoxicity by promoting AKT/GSK3β/β-catenin signaling, while it did not show cytotoxicity to normal cardiomyocytes in the 0–500 μg/ml dose range. After 7 days of administration to aged AMI rats, GBE80 markedly reduced the weight ratio of the infarction and inhibited cell apoptosis in myocardial tissue. Furthermore, the AKT/GSK3β/β-catenin signaling pathway was activated by GBE80. These results suggest that GBE80 injection effectively inhibited AMI-induced myocardial damage and in vitro H2O2-induced cardiomyocyte cytotoxicity by activating the AKT/GSK3β/β-catenin signaling pathway.